Eskatologi : Keberadaan Alam Akhirat dalam Al-Qur'an: Kajian Tafsir Analitik (Tahlili) Surat Ibrahim Ayat 48 - Abdul Majid; Ainul Yaqin (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2023)
Every living thing in this world will die. After life in this world, there is another life, namely life after death or life in the afterlife. Life after death or life in the afterlife has always been a mystery. It has always captured the imagination with various perceptions.  This research aims to explore the existence or location of the afterlife, based on the interpretation of Surah Ibrahim verse 48. This research uses the analytical interpretation method (tahlili) accompanied by a Sufi interpretation approach. This study shows the result that the existence of the afterlife itself occurs on this planet earth, namely in the place where humans are now. However, some interpretations describe differences regarding the mechanism of the changing of the earth and the ceiling and the description of the state of the times and the earth.